1994
DOI: 10.1007/bf01830725
|View full text |Cite
|
Sign up to set email alerts
|

Sugar, meat, and fat intake, and non-dietary risk factors for colon cancer incidence in Iowa women (United States)

Abstract: To investigate the relation of dietary intakes of sucrose, meat, and fat, and anthropometric, lifestyle, hormonal, and reproductive factors to colon cancer incidence, data were analyzed from a prospective cohort study of 35,215 Iowa (United States) women, aged 55-69 years and without a history of cancer, who completed mailed dietary and other questionnaires in 1986. Through 1990, 212 incident cases of colon cancer were documented. Proportional hazards regression was used to adjust for age and other risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
295
5
14

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(330 citation statements)
references
References 45 publications
16
295
5
14
Order By: Relevance
“…The prospective studies' results have been mixed. Some studies showed increased risk of cancer in the whole cohort with high glycemic load [18-20]; some studies found only increased risk among subgroups such as sedentary, overweight subjects [21-24]; other studies concluded that there was no increased risk for any of their cohort [25-28]. Even though there were no associations between glycemic load and colorectal, breast, or pancreatic cancer in the Nurses' Health Study there was still a strong link between diabetes and colorectal cancer [29].…”
Section: Reviewmentioning
confidence: 99%
“…The prospective studies' results have been mixed. Some studies showed increased risk of cancer in the whole cohort with high glycemic load [18-20]; some studies found only increased risk among subgroups such as sedentary, overweight subjects [21-24]; other studies concluded that there was no increased risk for any of their cohort [25-28]. Even though there were no associations between glycemic load and colorectal, breast, or pancreatic cancer in the Nurses' Health Study there was still a strong link between diabetes and colorectal cancer [29].…”
Section: Reviewmentioning
confidence: 99%
“…Recording of the antecedent diet is far less dependent on memory and cannot be distorted in response to the diagnosis. There are 14 cohort studies (Hirayama, 1990;Phillips & Snowdon, 1985;Heilbrun et al, 1989;Willett et al, 1990;Thun et al, 1992;Bostick et al, 1994;Giovannucci et al, 1994;Goldbohm et al, 1994;Knekt et al, 1994;Gaard et al, 1996;Kato et al, 1997;Hsing et al, 1998;Singh & Fraser, 1998;Jensen et al, 1999) in Table 2 based on a total of 1 492 308 subjects. This is a larger set than seven cohort studies for meat and colorectal cancer in the WCRF review and nine cohort studies reporting fresh meat or processed meat in the British COMA review.…”
Section: The Cohort Studiesmentioning
confidence: 99%
“…Height is affected not only by genetic factors, but also by nutritional condition during childhood and adolescent. Some studies Chute et al, 1991;Bostick et al, 1994;Giovannucci et al, 1995;Robsahm and Tretli, 1999;Smith et al, 2000), but not all (Okasha et al, 2000), have reported a positive association between height and colon cancer. Results of studies on body mass index (BMI) in relation to colorectal cancer have been also inconsistent.…”
mentioning
confidence: 99%